Pengaruh Komunikasi, Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai Kantor PT. Bank Sumsel Babel Cabang Penukal Abab Lematang Ilir - Anggun Prayogi; Fatimah Fatimah; Tobari Tobari (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to determine the effects of Motivation, Communication, and Work Discipline on the Performance of Employees at PT. Bank Sumsel Babel Penukal Abab Lematang Ilir Branch Office. This type of research is causally associated with quantitative techniques. The variables used in this study are Motivation, Communication, and Work Discipline, and their effects on the Performance of Employees at PT. Bank Sumsel Babel Penukal Abab Lematang Ilir Branch Office. The sample in this study consisted of 110 employees of PT Bank Sumsel Babel Penukal Abab Lematang Ilir Branch Office, selected using Cluster Random Sampling. The data used in this study are primary data collected through questionnaires. The data analysis technique used is Multiple Linear Regression in SPSS. The results of this study indicate that: (1) Communication has a positive and significant effect on employee performance. (2) Motivation does not have a positive and significant effect on employee performance. (3) Work discipline has a positive and significant effect on employee performance.